'Cultural making': how complexity and power relations are modulated in transdisciplinary research. Issue 4 (3rd July 2016) - Swist, Teresa; Hodge, Bob; Collin, Philippa
Abstract: There is an increasing adoption of large-scale, multisectoral collaborations which draw upon diverse expertise and innovative processes to tackle complex issues. How social change emerges through such transdisciplinary research alliances is the focus of our paper. Yet, broader participation and openness to uncertainty exacerbates issues of multidimensional power and complexity which continually shape and reshape practices. In this article, we introduce the term 'cultural making' to illustrate how complexity and power are modulated according to particular interrelationships, roles and understandings. These issues are examined from a particular vantage point, the needs and values of a research enterprise, the Young and Well Cooperative Research Centre (Young and Well CRC), and within that, the project Safe and Well Online. Themes of power and complexity are explored in relation to better fulfilling the major aim of Young and Well CRC: to understand and maximize the role of digital technologies to promote the mental health of young people. We demonstrate how the heuristic of 'cultural making' blends spatio-temporal critique with practical ontology to consider how proximities, methods and practices unfold within a transdisciplinary research initiative. This lens aims to enhance practical engagement with complexity through showing the changing composition of potentialities and actualizations – and that participation is always a 'matter of making'.